2009
DOI: 10.1902/jop.2009.090098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Antioxidant Defense Enzymes and RANKL Expression in Human Periodontal Ligament Cells

Abstract: Nicotine upregulated RANKL and antioxidant defense enzymes. These data suggest that Nrf2-mediated induction of cellular antioxidants and phase II enzymes could contribute to the cellular defense against nicotine-induced cytotoxicity and osteoclastic differentiation in PDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 22 publications
4
34
0
4
Order By: Relevance
“…Therefore, we used hPDLCs because these cells are involved in regulating alveolar bone metabolism. hPDLCs express osteoblast‐like properties, including the expression of ALP, OCN, and OPN [Lee et al, 2009]. In the present study, the mRNA expression levels of markers for osteoblastic differentiation, such as ALP, OCN, OPN were determined using a semi‐quantitative RT‐PCR method.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, we used hPDLCs because these cells are involved in regulating alveolar bone metabolism. hPDLCs express osteoblast‐like properties, including the expression of ALP, OCN, and OPN [Lee et al, 2009]. In the present study, the mRNA expression levels of markers for osteoblastic differentiation, such as ALP, OCN, OPN were determined using a semi‐quantitative RT‐PCR method.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in vitro studies have demonstrated that nicotine, a major component of cigarette smoke, inhibits the attachment and growth of human gingival fibroblasts (HGFs) and human periodontal ligament cells (hPDLCs) [Tipton and Dabbous, 1995; James et al, 1999]. Recently, we reported that nicotine treatment concomitantly downregulates osteoblastic differentiation markers, such as alkaline phosphatase (ALP), osteocalcin (OCN), and osteopontin (OPN), and upregulates the expression of receptor activator of nuclear factor‐κB ligand (RANKL) in hPDLCs [Lee et al, 2009].…”
mentioning
confidence: 99%
“…Die geringe, nicht signifikante Erhöhung des parodontalen Knochenverlustes könnte durch die für einen Rattenmolar, der gegenüber dem Menschen um einen Faktor von 50 kleiner ist [43], leicht supraphysiologische Kraft von 0,125 N zu erklären sein, die aus experimentell methodischen Gründen nicht weiter reduziert werden konnte, um die for IL-6. We also noticed dose-dependent stimulation of RAN-KL gene expression by nicotine associated with a simultaneous downregulation of OPG expression, which is consistent with findings by Lee et al [28] and might be a function of autocrine and paracrine stimulation of RANKL expression resulting from the enhanced PGE 2 and IL-6 synthesis by PDL cells [20,50]. In conjunction with the documented release of M-CSF [50], these phenomena would lead to increased differentiation of osteoclasts and resorption of peri-alveolar bone [17].…”
Section: Wirkung Kieferorthopädischer Kräfte Auf Das Parodontalligameunclassified
“…Ebenso fanden wir eine dosisabhängige Stimulation der RANKL-Genexpression bei gleichzeitiger Hemmung der OPG-Expression unter Nikotineinfluss. Dies deckt sich mit Untersuchungen von Lee et al [28] und könnte durch die auto-und parakrine Stimulation der RANKL-Expression über die erhöhte PGE 2 -und IL-6-Bildung von PDL-Zellen bedingt sein [20,50]. Zusammen mit der ebenfalls beschriebenen Freisetzung von M-CSF [50] führen diese Prozesse zu einer vermehrten Differenzierung von Osteoklasten und zu einer Resorption von perialveolärem Knochen [17].…”
Section: Compliance With Ethical Guidelinesunclassified
“…Nicotine was found to upregulate the expression of various osteolytic mediators, such as interleukin (IL)-1, IL-8, receptor activator of nuclear factor-kappa B/RANK ligand (RANKL), matrix metalloproteinase, and tissue-type plasminogen activator, and downregulate the expression of osteoprotegerin. [12][13][14] Most clinicians regard orthodontically induced root resorption as an inevitable sequela of OTM. The odontoclasts were reported to be responsible for the process of root resorption and share many features with osteoclasts, such as the expression of H + -ATPase, cathepsin K, matrix metalloproteinase-9, and so on.…”
Section: Introductionmentioning
confidence: 99%